The Italian urban landscape tradition. Sapienza University Campus and the shape of the green (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2024)
Between 1932 and 1935, Marcello Piacentini (1881-1960) was in charge of coordinating the project of the new University Campus of Rome. The modern Studium Urbis would have grouped the colleges located in the city center, creating dedicated buildings, and reducing together people's pressure on historical neighborhoods. Such an opportunity affected the design, suggesting the architect imagine an autonomous citadel inspired by American and European successful experiments: particularly, the campus of Madrid and the University of Virginia. Each building was entrusted to a professional. Piacentini managed the construction of the Rectorate, assigning the surrounding faculties and the access propylaea to his trusted studio collaborators to guarantee uniformity. In addition, Piacentini developed Sapienza’s master plan by referring to the Renaissance tradition, proposing a rigorous layout dominated by voids and greenery. He adopted a basilica plan, proportioning the transversal axis using the width of Piazza Navona as a model, and manipulated the orography to align the monumental university gate with the ground floor of the Rectorate. Finally, he took advantage of the expressive properties of the perspective methods, using both the trees and traditional visual devices to generate a controlled, linear, and monumental urban space.Keywords: Rome, Sapienza, Marcello Piacentini, cultural landscape, garden design